Coping styles, strategies and psychological distress amongst perinatal individuals during the COVID-19 pandemic: a rapid review - Papadopoulos, Alissa; Duerden, Emma G. (Frontiers in Global Women's Health, 2025)
IntroductionPerinatal individuals are at an increased risk of experiencing psychological distress, which often manifests in a combination of co-occurring symptoms of anxiety, depression, and stress. During the COVID-19 pandemic, the rates of psychological distress experienced by perinatal women dramatically increased, in some cases doubling or even tripling. This increase is concerning as psychological distress can impact the health and wellbeing of mothers and their offspring, including an offspring's neurocognitive, physical, mental, and socio-emotional development. The strategies a perinatal individual uses to cope with psychological distress are modifiable and, therefore, can be targeted to help improve outcomes for mothers and their offspring.MethodsThis rapid review describes and synthesizes the literature related to coping with perinatal psychological distress during the COVID-19 pandemic. This review included twenty-four cross-sectional studies.ResultsPerinatal individuals reported using various coping strategies to deal with the COVID-19 pandemic, including social strategies (e.g., connecting with others); physical strategies (e.g., exercising); cognitive strategies (e.g., positive re-appraisal); and spiritual strategies (e.g., prayer). An avoidant style of coping and its accompanying behaviours, including disengagement, substance use, and distraction via screen time/social media use, were significantly associated with higher levels of psychological distress. Strategies associated with lower levels of psychological distress included sleep and social support.DiscussionFuture studies should address the impact of technology on coping and the long-term impact of coping styles used during the COVID-19 pandemic on the wellbeing of mothers and their offspring. Although this rapid review centered on the COVID-19 context, its findings are broadly relevant to women worldwide who continue to experience prolonged stressors such as climate change, poverty, and conflict.